Pembentukan Identitas Organisasi Sebagai Penguatan Ketahanan Sosial: Studi Kasus RS PKU Muhammadiyah Yogyakarta - Siti Noordjannah Djohantini; Aqil Teguh Fathani; Musoli Musoli (Universitas Gadjah Mada, 2021)
This study examines and describes the process of establishing organizational identity as a means of enhancing social resilience; in this case the application of Al-Ma'un values as the organization's unique identity. This study concentrated on the Hospital Umamt Muhammadiyah in Yogyakarta (PKU). This research contributes theoretically to the development of organizational theory by focusing on the religiosity of organizational identity as a relatively new object of study in social sciences, particularly organizational social resilience.This study uses a qualitative case study method to obtain data, information, and knowledge related to members' awareness of Al-Ma'un, which was the source of inspiration for the birth of this hospital in 1923. Informants consisted of employees, with primary data collection through in-depth interviews.The findings indicated that Al-Ma'un members' identification with their values had been internalized into a nested identity that evolved into the organizational identity of PKU Muhammadiyah Hospital Yogyakarta. Theoretically, this study discovered a robust and enduring distinctive value for the three CED criteria (central, enduring, distinctive) in the concept of organizational identity, thereby supporting the value of social resilience. Al-Ma'un is what distinguishes PKU Muhammadiyah Hospital from other hospitals. However, the fact indicates that there is still some misalignment of values, as several health workers at PKU Muhammadiyah Hospital continue to exhibit inconsistent Islamic behavior.